2022
DOI: 10.1186/s12887-022-03504-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ideal cardiovascular health among Iranian adolescents: 2007–2008 to 2015–2017

Abstract: Background Assessment of both behavior and factors of health as ideal cardiovascular health (iCVH) in adolescence could contribute to cardiovascular disease prevention in adulthood. Aims To explore the changes in the prevalence of iCVH and its components during a decade among Tehranian adolescents. Methods The 12–19 years old adolescents were selected from the Tehran Lipid and Glucose Study(TLGS). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The large AVENA study ( 50 ) assessed more than 500 children and adolescents and found that the waist circumference and BMI increased in girls as puberty continued, while in boys there were no correlations with the pubertal stage. An increase in total body fat was observed in both females and males throughout puberty, and BMI increased through the 8–18 years interval of observation ( 51 ). This was largely driven by the increase in the lean component of BMI, particularly in boys ( 52 ).…”
Section: Obesitymentioning
confidence: 99%
“…The large AVENA study ( 50 ) assessed more than 500 children and adolescents and found that the waist circumference and BMI increased in girls as puberty continued, while in boys there were no correlations with the pubertal stage. An increase in total body fat was observed in both females and males throughout puberty, and BMI increased through the 8–18 years interval of observation ( 51 ). This was largely driven by the increase in the lean component of BMI, particularly in boys ( 52 ).…”
Section: Obesitymentioning
confidence: 99%